Preparación para la enseñanza de matemáticas básicas en la escuela: análisis de la competencia y la autoeficacia de los docentes en formación tras la enseñanza con apoyo en las escuelas - Baah-Duodu, Samuel (2025)
This study investigated the preparedness of pre-service teachers in colleges of education to teach mathematics by examining their mathematics proficiency and perceived self-efficacy after supported teaching in schools. The population for this study was 21,500 level 400 pre-service teachers from the 46 public colleges of education in Ghana. The quota purposive sampling technique was employed to select 390 pre-service teachers for the study. The design of the study integrated quantitative analysis based on a causal-comparative framework. Mathematics proficiency test and self-efficacy for teaching mathematics questionnaire were the instruments used to collect data. Data collected from the test and questionnaire was analysed quantitatively. Descriptive statistics was employed to analyse pre-service teachers’ levels of preparedness, proficiency and self-efficacy. Independent sample t-test and one-way ANOVA were used to find differences in proficiency, self-efficacy and preparedness. The findings revealed that pre-service teachers are moderately prepared with younger participants exhibiting higher levels of proficiency. Gender-related differences were noted in self-efficacy, with females demonstrating enhanced confidence while males demonstrated higher proficiency and preparedness. The findings underscore the importance of tailored training programmes for diverse age groups, ensuring gender-inclusive strategies to nurture self-confidence among all pre-service teachers.